Sustainability reporting and financial performance of listed financial firms in Kenya - Agutu, Omollo Joel; Githira, Wanyoike Charles (Journal of Accounting, Business and Finance Research, 2023)
Financial sector stability is vital for the realization of economic development. Failure to incorporate environmental, social and governance (ESG) elements into corporate strategies can lead to corporate failure. Through the adoption of a descriptive research design, this study aims to determine the relationship between sustainability reporting and the financial performance of financial companies listed on the Nairobi Securities Exchange (NSE) in Kenya. Through the census method, the study population of twenty-three listed financial firms was obtained, and secondary data for the period from 2015 to 2021 was extracted through content analysis. Data on predictor variables were obtained through a document check index utilizing a non-refined exploratory factor analysis, while data on the response variable were obtained directly from annual reports. The data were analyzed through descriptive and inferential statistics. Modelling was further adopted through feasible generalized least squares (FGLS) to counter the problem of first order serial correlation. The findings indicate a positive and significant relationship between ESG reporting and the financial performance of listed financial firms in Kenya. The results imply that firms should embrace sustainability since ESG drives corporate strategies and will help firms to improve their performance, which will bring improved resilience. Focus on the triple bottom line enables value maximization for the three Ps – profit, people, and planet – thus facilitating sustainable development. The harmonization of reporting guidelines which is process-driven rather than content-driven will minimize greenwashing by firms. Lastly, industry players should ensure the availability and quality of ESG data.